Enantioselective Synthesis of α‐Aryl‐β2‐Amino‐Esters by Cooperative Isothiourea and Brønsted Acid Catalysis. Issue 21 (4th May 2021) - Zhao, Feng; Shu, Chang; Young, Claire M.; Carpenter‐Warren, Cameron; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract: The synthesis of α‐aryl‐β 2 ‐amino esters through enantioselective aminomethylation of an arylacetic acid ester in high yields and enantioselectivity via cooperative isothiourea and Brønsted acid catalysis is demonstrated. The scope and limitations of this process are explored (25 examples, up to 94 % yield and 96:4 er), with applications to the synthesis of ( S )‐Venlafaxine⋅HCl and ( S )‐Nakinadine B. Mechanistic studies are consistent with a C(1)‐ammonium enolate pathway being followed rather than an alternative dynamic kinetic resolution process. Control studies indicate that (i) a linear effect between catalyst and product er is observed; (ii) an acyl ammonium ion can be used as a precatalyst; (iii) reversible isothiourea addition to an in situ generated iminium ion leads to an off‐cycle intermediate that can be used as a productive precatalyst. Abstract : An operationally simple and effective catalytic enantioselective approach to α‐aryl‐β 2 ‐amino esters is demonstrated and applied to the synthesis of ( S )‐Venlafaxine⋅HCl and ( S )‐Nakinadine B. Mechanistic investigations support a C(1)‐ammonium enolate pathway with reversible isothiourea addition to an in situ generated iminium ion leading to an off‐cycle intermediate that can be used as a productive precatalyst.